Self-efficacy, professional ethics, and internal audit quality - Syahril Djaddang; Shanti Lysandra (Jurnal Ekonomi dan Bisnis, 2022)
This study aims to investigate the effects of self-efficacy and professional ethics on internal audit quality and the role of professional ethics in moderating the relationship between self-efficacy and internal audit quality. We use the purposive sampling method to generate the sample from the internal auditors of Bogor City, resulting in 38 final samples. The findings demonstrate that both self-efficacy and professional ethics significantly affect internal audit quality, and professional ethics fully moderate the relationship between self-efficacy and internal audit quality. Thus, our results imply that the Indonesian governments (both at central and local levels) need to enhance their internal auditors' self-efficacy and professional ethics to improve internal audit quality in the public sector.